2023
DOI: 10.3390/toxics11110897
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Prenatal Exposure to Per- and Polyfluoroalkyl Substances and Respiratory Tract Infections in Preschool Children: A Wuhan Cohort Study

Haiyun Huang,
Xiaojun Li,
Yican Deng
et al.

Abstract: This study investigates the association between prenatal exposure to per- and polyfluoroalkyl substances (PFASs) and the incidence and frequency of respiratory tract infections (RTIs) in preschool children. We selected 527 mother–infant pairs from Wuhan Healthy Baby Cohort (WHBC), China. Ten PFASs were measured in umbilical cord serum, and we collected data on common RTIs in preschool children aged 4 years through a questionnaire. Associations of single PFASs with the incidence and frequency of RTIs were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…PFAS are a structurally diverse class of chemicals, with some substances showing stability in the environment and some showing bioaccumulative properties (or potential), with half-lives in humans up to several years [3,4]. There is increasing evidence that some PFAS cause health effects, including immunotoxicity, developmental and reproductive effects, increased BMI, decreased birthweight, and cancer [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18]. These conclusions arise from epidemiology studies that have shown correlations between the levels of PFAS in the environment (e.g., drinking water) and levels of incidence of certain health effects (many of the previously cited references), plus experimental studies on animals [19].…”
Section: Introductionmentioning
confidence: 99%
“…PFAS are a structurally diverse class of chemicals, with some substances showing stability in the environment and some showing bioaccumulative properties (or potential), with half-lives in humans up to several years [3,4]. There is increasing evidence that some PFAS cause health effects, including immunotoxicity, developmental and reproductive effects, increased BMI, decreased birthweight, and cancer [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18]. These conclusions arise from epidemiology studies that have shown correlations between the levels of PFAS in the environment (e.g., drinking water) and levels of incidence of certain health effects (many of the previously cited references), plus experimental studies on animals [19].…”
Section: Introductionmentioning
confidence: 99%